Ethnobotany of wild edible plants by the community of Cijambu Village, Sumedang District, West Java, Indonesia - AFDILAH ALFINANDAH; BUDI IRAWAN; JOHAN ISKANDAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Alfinandah A, Irawan B, Iskandar J. 2025. Ethnobotany of wild edible plants by the community of Cijambu Village, Sumedang District, West Java, Indonesia. Biodiversitas 26: 2235-2252. Wild plants that can be consumed have been widely utilized as food and medicine by communities in various regions in Indonesia. The utilization by the Sundanese community in West Java may differ from other regions due to variations in Traditional Ecological Knowledge (TEK) and diverse traditions. This research was conducted in Cijambu Village, Tanjungsari Sub-district, Sumedang District, West Java, Indonesia. This study employs a mixed qualitative and quantitative method with an ethnobotanical approach. The results of this study show that 48 species, belonging to 31 families, with the most commonly found family being Asteraceae. The results of the analysis included Use Value (UV), with Bambusa vulgaris having the highest value at 0.08. Amaranthus viridis has the highest Relative Frequency Citation (RFC) value of 0.8. A total of 18 species of Wild Edible Plants (WEPs) are used as food sources, while 20 types of diseases are reported to be treated using WEP. Twelve species of WEP were specifically used for medicinal purposes, the results of the Informant Consensus Factor (ICF) analysis showed the highest value of 0.2 for Blumea balsamifera. Eighteen species are used both as food and medicine, often consumed simultaneously. The most widely used part of WEP is the leaves, followed by flowers, fruits, roots, stems, shoots and bulbs. The traditional processing of WEP by the community is vegetables (angeun), salad (lalap), stir-fry (oséng), steamed (seupan, urap, botok, karédok, buntil, lompong) and herbal tea. Therefore, WEP in rural areas can play a role in supporting SDGs programs, such as ending poverty in all forms everywhere (SDGs No. 1), ending hunger, achieving food security and improving nutrition as well as promoting sustainable agriculture (SDGs No. 2) and ensuring healthy lives and supporting welfare for all ages (SDGs No. 3).